Modernity and Sexual Identity in Mexican Literature of the Early 20th Century. - Hernández, Rafael (2008)
Keywords: dept.wll; faculty_collection; sabbatical_report

Report of the Activities Completed During Sabbatical Leave in the Fall of 2007. - Schmitt, Elena (Distribution: Fall 2007 ; World Languages and Literatures., 2007)
Research completed during this leave focused on the already collected data for an article outlining distinctions between language attrition and incomplete acquisition, and on a new project and new data for research on how literacy or its lack in a minority language affects the degree of language maintenance and development.
Keywords: dept.wll; faculty_collection; sabbatical_report

Creating the Slavic Peril. - Paddock, Troy R. E. (2004)
Keywords: dept.wll; faculty_collection; sabbatical_report

The Literature of the Colombian Pacific Coast and the Construction of a Cultural Identity. - Arboleda, Carlos (2002)
Keywords: dept.wll; faculty_collection; sabbatical_report

Textual Experimentations in Contemporary Mexico. - Pelayo, Ruben (Fall;Foreign Language., 2001)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Researched and translated two early twentieth-century plays] - Vena, Michael (Fall;Foreign Language., 2001)
Keywords: dept.wll; faculty_collection; sabbatical_report

[Wilhelm August Lehmann, 1870-1934] - Brockhagen, Marga (Fall;Foreign Language., 2000)
Keywords: dept.wll; faculty_collection; sabbatical_report

Gabriel García Márquez: A Biography - Pelayo, Rubén (Greenwood Press, 2009)
Keywords: 20th century; Biography; García Márquez; Gabriel; 1927-2014; Authors; Colombian; dept.wll; faculty_collection

Inclusive Pedagogy for English Language Learners: A Handbook of Research-Informed Practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Lawrence Erlbaum Associates, 2008)
Keywords: English language; Foreign speakers; English language; Foreign speakers; Language and languages; Study and teaching; Study and teaching (Elementary); Study and teaching (Secondary); dept.wll; faculty_collection

The impact of Don Quixote (1605-2005) on the culture of the modern and postmodern world: proceedings of the Southern Connecticut State University International Conference on Don Quixote, New Haven, April 22-23, 2005 - Southern Connecticut State University International Conference on Don Quixote New Haven, Conn) (Southern Connecticut State University, 2006)
Keywords: Cervantes Saavedra; Miguel de; 1547-1616. Don Quixote; Congresses; Postmodernism; dept.wll; faculty_collection

Agítese Bien: A New Look at the Hispanic Avant-Gardes - Pao, María T.; Hernández Rodríguez, Rafael (Juan de la Cuesta, 2002)
Keywords: 20th century; History and criticism; History and criticism; Latin American literature; History and criticism; Literature; Experimental; History and criticism; Spanish American literature; Latin America; Spain; Spanish literature; dept.wll; faculty_collection

Gabriel García Márquez: A Critical Companion - Pelayo, Rubén (Greenwood Press, 2001)
Keywords: Criticism and interpretation; García Márquez; Gabriel; 1927-2014; dept.wll; faculty_collection

Italian Grotesque Theater - Vena, Michael (Fairleigh Dickinson University Press, 2001)
SCSU Faculty Scholar Award
Keywords: 20th century; History and criticism; Grotesque in literature; Italian drama; award_winner; dept.wll; faculty_collection

Second and Foreign Language Learning Through Classroom Interaction - Hall, Joan Kelly; Verplaetse, Lorrie Stoops (Erlbaum, 2000)
This volume brings together the current theoretical interest in reconceptualizing second and foreign language learning from a sociocultural perspective on language and learning, with practical concerns about second and foreign language pedagogy. It presents a set of studies whose focus is on the empirical description of particular practices constructed in classroom interaction that promote the learning of a second or foreign language. The authors examine in detail the processes by which the learning of additional languages is accomplished in the interaction of a variety of classrooms and in a
Keywords: Language and languages; Study and teaching; Interaction analysis in education; dept.wll; faculty_collection

Voices in Dialogue: Reading Women in the Middle Ages - Olson, Linda; Kerby-Fulton, Kathryn (University of Notre Dame Press, 2005)
Keywords: History; History and criticism; Civilization; Medieval; Middle Ages; 500-1500; Women and literature; To 1500; Literature; Medieval; Women; dept.wll; faculty_collection

Of courtesans, knights, cooks and writers: Food in the renaissance - Palma, P. (MLN - Modern Language Notes, 2004)
0 citations (Crossref) [2023-10-31]
Keywords: dept.wll

The evolving door: providing technology access for post-secondary students in a constantly changing technology-based culture - Hecht, Janice; Zamfir, Bogdan (International Conference on Computers Helping People with Special Needs, 2002)
The Center for Adaptive Technology at Southern Connecticut State University was established in 1988 to provide access to computers for students with disabilities. The challenge of keeping current with both standard and adaptive technology has caused our service to evolve from a focused, centralized model to an integrated model providing technology access to students regardless of their location on campus. © Springer-Verlag Berlin Heidelberg 2002.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Adaptive technology; Artificial intelligence; Centralized models; Computer science; Computers; Integrated modeling; Students; Technology-based; dept.wll

Fifty Strategies for Teaching English Language Learners.: Adrienne L. Herrell - Reynolds, Kate Mastruserio (TESOL Quarterly, 2001)
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000168531300015, lens.org/044-748-807-257-656, pop00009 tex.unique-id: [object Object]
Keywords: dept.wll

Out of Africa - Feinberg, H.M.; Solodow, J.B. (Journal of African History, 2002)
This article traces the origins of the familiar quotation, 'there is always something new coming out of Africa'. It demonstrates that the phrase was a proverb that originated in Greece no later than the fourth century BC. It charts the transmission of the phrase from Aristotle to the twentieth century, noting that Erasmus is the most important link in the Renaissance and that he may be responsible for the current form in which the phrase is used. The article also shows that the meaning of the phrase was very different in ancient times from what it is today. Whereas 'something new' to Aristotle meant strange hybrid animals, current writers use the phrase with a sense of admiration.
9 citations (Crossref) [2023-10-31]
Keywords: Africa; Historiography; dept.his; dept.wll; history; perception; regional geography